The Influence of Principal Leadership, Teacher Work Motivation, and School Culture on the Professional Competence of State Vocational High School Teachers in Jepara Regency with Rewards as a Moderating Variable - Heri Kusdiyanto; Titi Prihatin (Universitas Negeri Semarang, 2026)
Teacher professional competence is the main determinant of the quality of vocational education and is crucial for State Vocational High Schools in Jepara Regency in facing the challenges of the modern era, especially related to competency renewal, creativity, and suboptimal technology adaptation among some teachers. This study aims to analyze the partial influence of principal leadership, teacher work motivation, and school culture on teacher professional competence, as well as the role of rewards as a moderating variable. Quantitative research methods were used with a population of teachers and a sample of teachers from State Vocational High Schools. Data collection was carried out through a questionnaire instrument, and analyzed using multiple regression, Moderated Regression Analysis, and partial t-test. The results showed that principal leadership, teacher work motivation, and school culture partially have a positive and significant effect on teacher professional competence, where work motivation shows the most dominant influence. An important finding is that rewards are proven to be able to moderate and strengthen the relationship between principal leadership and school culture on teacher professional competence, but do not moderate the effect of teacher work motivation. The coefficient of determination indicates that the variation in teachers' professional competence can be explained by the independent variables. This finding contributes to emphasizing the need for an integrated reward system to optimize the impact of organizational factors in improving teacher professionalism.